Розробка концепції спеціалізованої бази знань як засобу комплексної структуризації простору рішень технологічних задач - Ковальчук, С. С.; Мазурець, О. В. (НТУ "ХПІ", 2009)
In the article with position of the system approach are described principle, structure and perspectives of the use specialized knowledge base as facility complex structurization of decision space of the technological problems. On example of the successful using stated concepts specialized knowledge base for decision of the actual problems of using CAD and CADTP, is proved efficiency and perspectiviency described methodiks.
Keywords: системний підхід; ієрархічна структура; технологічні задачі; метод зберігання моделей